Entrepreneurship as a tool for women empowerment in Nigeria - Oluwakemi, Rachael Adeleye; Koponics Györke, Diána; Gubacsi, Franciska (Studia Mundi – Economica, 2023)
Women entrepreneurship is one of the key areas in advancing gender equality and achieving economic empowerment among women. The women empowerment topic which stems from the SDGs 5 of gender equality is known to be one of the ways through which long term economic success can be achieved in many nations of the world. A means of achieving this is through female entrepreneurships which provide the economic stability and strength for many women and help them become independent. Women entrepreneurs account for up to a third of all businesses operating in the formal economy worldwide, however, the majority of those in developing and transitioning economies are very small and micro enterprises, with little potential for growth most especially among the female gender. Female entrepreneurship in Nigeria has often been driven by necessity and seen as a norm in emerging markets due to insufficient formal employment. Nigerian women involved in entrepreneurs are being faced with many challenges which ranges from lack of access to funds, infrastructures, entrepreneurial trainings, and small business sizes, which calls for urgent need, intervention, and appropriate measures by government. This study examined the importance of women entrepreneurship in Nigeria, it further gave a breakdown of the labor force in the aspect of women participation, the entrepreneurial reasons women venture into businesses and what strategies could be implemented to create enabling environment for female in businesses and positive impact on women empowerment in the country.